Knowledge, Attitude and Behavior of Social Forestry Groups Members towards Mitigation Actions in the Forestry Sector - Utami, Mega Rita; Wildayana, Elisa; Hadinata, Febrian (Journal La Lifesci, 2024)
Social Forestry Groups (KPS) are the main target for implementing forestry sector mitigation activities at the site level, therefore the success of forestry sector mitigation is largely determined by the contribution of KPS involvement. The purpose of this study is to analyze whether the mitigation activities will be successfully implemented by KPS by measuring knowledge, attitudes, behaviors associated with the role of each member in the KPS institution and how the performance of the KPS is good or still needs to be improved. This study was conducted in the Management Area of UPTD KPH Region XI Kikim Pasemah with the research objects of KTH Luang Kering and KTH Sungai Geruntang from July to September 2023. The research method used is a descriptive method with a qualitative approach. The results of the study showed that the level of knowledge of KPS members regarding climate change (10.42%) and mitigation (12.5 %). The respondents' attitudes showed a positive response to forestry sector mitigation activities (T Score> 50%). The behavior of most respondents towards the implemantation of mitigation activities by groups is not good, even though their attitudes support the implementation of mitigation actions, they stil play participatory role in climate change mitigation activities.